Inhibition of Glomerular Mesangial Cell Proliferation by siPDGF-B- and siPDGFR-beta-Containing Chitosan Nanoplexes - ÖZBAŞ, SUNA (SPRINGER, 2017)
Mesangioproliferative glomerulonephritis is a disease that has a high incidence in humans. In this disease, the proliferation of glomerular mesangial cells and the production of extracellular matrix are important. In recent years, the RNAi technology has been widely used in the treatment of various diseases due to its capability to inhibit the gene expression with high specificity and targeting. The objective of this study was to decrease mesangial cell proliferation by knocking down PDGF-B and its receptor, PDGFR-beta. To be able to use small interfering RNAs (siRNAs) in the treatment of this disease successfully, it is necessary to develop appropriate delivery systems. Chitosan, which is a biopolymer, is used as a siRNA delivery system in kidney drug targeting. In order to deliver siRNA molecules targeted at PDGF-B and PDGFR-beta, chitosan/siRNA nanoplexes were prepared. The in vitro characterization, transfection studies, and knockdown efficiencies were studied in immortalized and primary rat mesangial cells. In addition, the effects of chitosan nanoplexes on mesangial cell proliferation and migration were investigated. After in vitro transfection, the PDGF-B and PDGFR-beta gene silencing efficiencies of PDGF-B and PDGFR-beta targeting siRNA-containing chitosan nanoplexes were 74 and 71% in immortalized rat mesangial cells and 66 and 62% in primary rat mesangial cells, respectively. siPDGF-B- and siPDGFR-beta-containing nanoplexes indicated a significant decrease in mesangial cell migration and proliferation. These results suggested that mesangial cell proliferation may be inhibited by silencing of the PDGF-B signaling pathway. Gene silencing approaches with chitosan-based gene delivery systems have promise for the efficient treatment of renal disease.
Keywords: chitosan; glomerular mesangial cell; PDGF-B; PDGFR-beta; siRNA; MOLECULAR-WEIGHT CHITOSAN; ENDOTHELIAL GROWTH-FACTOR; N-SUCCINYL-CHITOSAN; SIRNA DELIVERY; NANOPARTICLE FORMULATION; DRUG CARRIER; PDGF; RECEPTOR; RAT; EXPRESSION